Modelling the distribution of forest pest natural enemies across invaded areas: Towards understanding the influence of climate on parasitoid establishment success - Fischbein, Deborah; Lantschner, Maria Victoria; Corley, Juan Carlos (Elsevier, 2019)
Classical biological control is a pest management practice frequently deployed against invasive insects. However, introduced natural enemies too often fail to establish, and this has been partly explained by climatic mismatching. We evaluate climate matching (using MaxEnt) for three parasitoids, Megarhyssa nortoni, Ibalia leucospoides and Rhyssa persuasoria, released in classical biological control programmes of the pine pest Sirex noctilio in the Southern Hemisphere and explore how climatic factors can influence parasitoid establishment success. Model predictions are compared against data on historical releases in this region. The main results show that for I. leucospoides and M. nortoni the eco-climatic distribution model successfully predicted the establishment in all the regions where the species are currently present. Additionally, for M. nortoni, the model also correctly predicted the regions where the species was released and failed to establish, as is the case of the south of Brazil and the Western Cape, South Africa. However, R. persuasoria established only in some of the regions where the model predicted its presence. These results highlight the usefulness of climatic matching techniques as an effective way to prioritize suitable areas to release specific biological control agents. However, climatic matching modelling does not always guarantee establishment, and likely, several other factors explain failures in establishing populations after releases. Further understanding of the factors affecting success in biological control programs of forest insects at a broad spatial scale may contribute to improve pest management skills of new and established populations of non-native forest insects.